2020
DOI: 10.24875/acme.m20000119
|View full text |Cite
|
Sign up to set email alerts
|

Venoarterial extracorporeal membrane oxygenation as a bridge to recovery in refractory cardiogenic shock secondary to fulminant influenza A myocarditis complicated with cardiac tamponade

Abstract: Oxigenador extracorpóreo de membrana venoarterial como puente a la recuperación en choque cardiogénico resistente secundario a miocarditis fulminante por virus de la influenza A complicada con taponamiento cardíaco

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Our literature review identified 75 unique cases (55 adult and 20 pediatric patients) from 56 case reports, and 5 case series describing 2 to 8 patients each, published from 1959 through 2021 [ 2 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 75 unique cases (55 adult and 20 pediatric patients) from 56 case reports, and 5 case series describing 2 to 8 patients each, published from 1959 through 2021 [ 2 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…A literature review of transient ventricular wall thickening associated with influenza myocarditis or myopericarditis reveals a handful of cases diagnosed on cardiac imaging [ 6 , 16 , 17 , 18 , 19 , 20 ] or autopsy [ 21 ]. Reversal of wall thickening was observed in all recovered cases within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%